2019
DOI: 10.1002/fsn3.1126
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance and genetic diversity of Salmonella enterica from eggs

Abstract: Salmonella enterica is a common foodborne pathogen responsible for major global health problems such as paratyphoid fever and gastroenteritis. Here, we report the prevalence, antibiotic resistance phenotypes, serotypes, and molecular subtyping of Salmonella isolated from eggs in Guangdong, China. Out of 1,000 egg samples, 54 (5.40%) were positive. S. Enteritidis made up the largest proportion of samples with 11 serotypes. Antimicrobial susceptibility test indicated that most strains were resistant to β‐lactam,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 29 publications
5
14
3
Order By: Relevance
“…In the present study, the overall prevalence of Salmonella was 7.78%, which were similar or in agreement with reports by Samanta et al [17]; Islam et al [18] and Xie et al [19]. Samata et al [17] identified 10% of Salmonella from backyard poultry eggs in West Bengal, India.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, the overall prevalence of Salmonella was 7.78%, which were similar or in agreement with reports by Samanta et al [17]; Islam et al [18] and Xie et al [19]. Samata et al [17] identified 10% of Salmonella from backyard poultry eggs in West Bengal, India.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, antibiotic sensitivity and resistance patterns of Salmonella to different antimicrobials are in harmony with previous reports by Islam et al [18]; Ugwu et al [26] and Xie et al [19]. Islam…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Generally, our results were consistent with the results of previous studies reporting that S. Typhimurium was the most prevalent serotype in eggs obtained from Penang in Malaysia and 50 poultry farms throughout Korea ( Adzitey et al, 2012 ; Bae et al, 2013 ). Additionally, S. Indiana, S. Typhimurium, and S. Enteritidis were found to be the predominant Salmonella serovars in eggs sampled in Yangzhou, China ( Li et al, 2017 ), while S. Enteritidis was the most prevalent serotype in eggs collected from Shandong, Shanghai, and Guangdong in China ( Ni et al, 2018 ; Xie et al, 2019 ; Yang et al, 2019 ). Particularly, S. Enteritidis has always been a common foodborne pathogen associated with salmonellosis caused by consumption of contaminated eggs or egg products, and this is mainly due to its specific survival mechanism in egg white with the assistance of the outer membrane channel TolC ( Huang et al, 2019 ; Raspoet et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have characterized Salmonella in poultry and poultry-associated foods globally, especially eggs ( Moffatt et al, 2017 ; Kouam et al, 2018 ; Li et al, 2018 ; FDA, 2019a , b , c ; Karimiazar et al, 2019 ; Kingsbury et al, 2019 ; Sanchez-Salazar et al, 2019 ). Evidence suggests that the genetic diversity of Salmonella isolated from various sources is abundant, whereas the isolates from the same poultry farms are closely related ( Xie et al, 2019 ). Moreover, the occurrence and characteristics of Salmonella in poultry products including eggs always show dynamic variation during production, storage, and handling ( Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%